Scientific Achievements in the Study of the Occurrence and Antimicrobial Susceptibility Profile of Major Foodborne Pathogenic Bacteria in Foods and Food Processing Environments in Romania: Review of the Last Decade. (24th June 2020) - Imre, Kálmán; Herman, Viorel; Morar, Adriana
Abstract : Pathogenic bacteria are recognized as a major cause of foodborne diseases in humans, globally, with negative impact on the economy of each country. The aim of the present review was to obtain a comprehensive understanding about the frequency of isolation, diversity, and antimicrobial susceptibility profile of the six major foodborne pathogenic bacteria in food matrices and food processing environment, in Romania. In this regard, results of relevant epidemiological studies, published during the last decade and retrieved from the Web of Science Core Collection database, were analyzed, with special emphasis on scientific achievements, main knowledge gaps, and future perspectives. The summarized and harmonized results offer useful insight, especially for public health authorities and researchers, having a reference effect in stimulating further opportunities for studies to be carried out to address some of the limitations of the current status.